2011
DOI: 10.1016/j.chom.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Perinuclear Filamentous Actin in Spatial Repositioning and Mutually Exclusive Expression of Virulence Genes in Malaria Parasites

Abstract: Many microbial pathogens, including the malaria parasite Plasmodium falciparum, vary surface protein expression to evade host immune responses. P. falciparium antigenic variation is linked to var gene family-encoded clonally variant surface protein expression. Mututally exclusive var gene expression is partially controlled by spatial positioning; silent genes are retained at distinct perinuclear sites and relocated to transcriptionally active locations for monoallelic expression. We show that var introns can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 41 publications
1
90
0
3
Order By: Relevance
“…Silent var genes seem to be associated with telomeric clusters at the nuclear periphery (46) and, when activated, reposition to a different location at the nuclear periphery (47). var positioning at the nuclear periphery was shown to be mediated by the interaction of nuclear actin and a conserved element found in var introns (20). In parasites in which mutually exclusive expression was partially disrupted by deletion of one intron, two active var genes colocalized to a distinct focus at the nuclear periphery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Silent var genes seem to be associated with telomeric clusters at the nuclear periphery (46) and, when activated, reposition to a different location at the nuclear periphery (47). var positioning at the nuclear periphery was shown to be mediated by the interaction of nuclear actin and a conserved element found in var introns (20). In parasites in which mutually exclusive expression was partially disrupted by deletion of one intron, two active var genes colocalized to a distinct focus at the nuclear periphery.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike var promoters, the DNA sequence of all intron promoters is highly conserved and cannot be classified into subgroups (15,19). var introns also contain a specific proteinbinding element that plays a role in positioning var genes at the nuclear periphery through interaction with nuclear actin (20).…”
mentioning
confidence: 99%
“…In addition, recent advances that allow specific visualization of filamentous actin (F-actin) indicated that F-actin fibers concentrate at discrete zones at the nuclear periphery in early stages of parasite development (merozoites and rings) (Angrisano et al, 2012). F-actin was also implicated in gene positioning at the nuclear periphery (Zhang et al, 2011) in early ring stages. In addition, in S. cerevisiae F-actin was found to be responsible for NPC dynamics (Steinberg et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Additional proteins, PFI0250c and PF14_0706 were suggested as Nup candidates in P. falciparum and polyclonal antibodies that were raised against single peptides of each of these genes were used as nuclear periphery markers (Volz et al, 2010;Zhang et al, 2011). The inefficiency of the simple sequence analysis to identify Nups homologs in P. falciparum might indicate that some Nups could have evolved differently to function as more than one Nup as suggested for PfSec13 or that evolutionarily distinct organisms have different nucleoporin repertoires as was shown in plants (Tamura et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation